2013
DOI: 10.1007/s11920-013-0360-9
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Neuroimaging Biomarkers in Geriatric Psychiatry

Abstract: Neuroimaging, both structural and functional, serve as useful adjuncts to clinical assessment, and can provide objective, reliable means of assessing disease presence and process in the aging population. In the following review we briefly explain current imaging methodologies. Then, we analyze recent developments in developing neuroimaging biomarkers for two highly prevalent disorders in the elderly population- Alzheimer's disease (AD) and late-life depression (LLD). In AD, efforts are focused on early diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…One study observed that lower 5-HTT transporter density was correlated with greater depression symptom severity [ 52 ]. These findings are in contrast to late-life major depression, including the observations of greater white matter hyperintensities, increased cortical glucose metabolism, and 5-HTT and 5-HT1A receptor loss, reviewed in Khandai and Aizenstein [ 53 ] (2013) and Hirao and Smith [ 54 ] (2014). Thus, the evidence indicates that decreased monoaminergic neurotransmitter function and decreased fronto-parietal metabolism are involved in mechanisms of depression in AD and that the metabolic changes are opposite to those observed in late-life major depression.…”
Section: Neurobiology Of Neuropsychiatric Symptoms Of Alzheimer’s Dismentioning
confidence: 99%
“…One study observed that lower 5-HTT transporter density was correlated with greater depression symptom severity [ 52 ]. These findings are in contrast to late-life major depression, including the observations of greater white matter hyperintensities, increased cortical glucose metabolism, and 5-HTT and 5-HT1A receptor loss, reviewed in Khandai and Aizenstein [ 53 ] (2013) and Hirao and Smith [ 54 ] (2014). Thus, the evidence indicates that decreased monoaminergic neurotransmitter function and decreased fronto-parietal metabolism are involved in mechanisms of depression in AD and that the metabolic changes are opposite to those observed in late-life major depression.…”
Section: Neurobiology Of Neuropsychiatric Symptoms Of Alzheimer’s Dismentioning
confidence: 99%
“…Neuroimaging and neurophysiological techniques have grown considerably in the past decade. Research continues to demonstrate their use for providing important information about the brain's structure and function (Khandai and Aizenstein, 2013). Brain imaging is often used to detect neurological causes (e.g., tumors, stroke), but not psychopathology (Vernooij et al, 2019).…”
Section: Neuroimaging and Neurophysiological Data (Table 1 Section C)mentioning
confidence: 99%
“…Brain morphometry is expected to become an essential quantitative neuroimaging biomarker (23). Although currently mainly used in the academic realm, it has great potential to complement today's predominantly qualitative visual assessments of MRI by neuroradiologists.…”
Section: Introductionmentioning
confidence: 99%